An Economic Magnetic Adsorbent for Acid Blue 80 and Methylene Blue Removal. Issue 31 (19th August 2019) - Ren, Zongli; Wang, Yahui; Fei, Peng; Liu, Xianyi; Jing, Wangli; Wang, Wei
Abstract: For the large volumes of dye wastewater treatment, the development of novel adsorbents with high adsorption capacity and good separation is of great significance. Here, a simple method is used to prepare a magnetic adsorbent for the efficient removal of acid blue 80 (AB‐80) and methylene blue (MB). The magnetic adsorption results show that as‐obtained MEL−Fe‐C exhibits good magnetic properties in AB‐80 and MB removal experiments. Importantly, this material shows good AB‐80 and MB removal property after ten times of repeated use. Therefore, as‐prepared MEL−Fe‐C is an ideal adsorbent candidate for removal of dyes in wastewater treatment applications. Abstract : Development of novel adsorbents with high adsorption capacity and good separation is an absolute requirement for treating large volumes of dye wastewater. Here, an economic magnetic adsorbent, MEL−Fe‐C, was prepared by a simple process. MEL−Fe‐C exhibits good magnetic properties and removes acid blue 80 and methylene blue to a large extent from water even after ten times of repeated use. Hence, it would be an ideal adsorbent candidate for removal of dyes during wastewater treatment.